SHALAT DAN KECEMASAN : KAJIAN ISLAM DAN PSIKOLOGI - Herlina Oktaviani herlinaoktaviani@upi.edu; Akmal Chandra Kusuma; Danar Hadi Khoerul Hakim; Neza Silma Neza Silma; Saepul Anwar (Pusat Studi GESI - UWP, 2023)
Prayer is a central practice of worship in the Islamic religion, while anxiety is a common problem among university students. Therefore, this research is important because it can provide valuable insights into how prayer can affect anxiety levels in Muslim students. Thus, this study aims to explore and understand the relationship between anxiety and prayer in the perspective of Muslim individuals majoring in Psychology at the Indonesian University of Education. This study also used a qualitative approach by conducting in-depth interviews and content analysis on the collected data. Research participants consisted of 7 active Muslim students who were selected purposely. Through qualitative data analysis, the following findings have been identified. Based on the results of interviews, all student informants had experienced anxiety, but the intensity and factors that caused anxiety felt by informants were different. Factors that cause anxiety felt by informants include academic problems, daily needs, family, friendships, and the future. This study provides a preliminary understanding of the relationship between prayer and anxiety in Muslim students. In order to deepen and complete this understanding, future researchers are advised to use quantitative methods in order to more objectively measure prayer frequency, anxiety level, and other factors that might affect this relationship.Kata kunci : Anxiety, Prayer, Student